Mechanical performance of hybrid glass/kenaf epoxy composite filled with organomodified nanoclay - Tay, Chai Hua; Mazlan, Norkhairunnisa; Hameed Sultan, Mohamed Thariq; Abdan, Khalina; Lee, Ching Hao (Elsevier Editora, 2021)
As increasing environmental awareness drives the development of biocomposites, the reality is that these material are still far behind in terms of application. While modifications on biocomposites do improve its properties, they are often conducted individually per study and not altogether, which may limit its potential. To expand the marketability of biocomposites, this research covers the hybridization of natural and synthetic fibre, reinforcement of Sodium Hydroxide (NaOH) treated kenaf fibre, reinforcement of organomodified nanoclay, and the use of modified epoxy in the production of the biocomposite. The dispersion of nanoclay in modified epoxy was conducted via sonication while the selected composite fabrication method is hand lay-up. In the flexural test, treated kenaf composites increase by 52% in flexural strength and 46% in flexural modulus, while treated nanocomposites improve by 83% in impact absorbed energy. The rough surface of treated kenaf and fractured composite surface can be seen using a Field Emission Scanning Electron Microscope (FESEM), indicating high interfacial adhesion in treated kenaf composites. Spectroscopy investigation utilising Fourier Transform Infrared (FTIR) revealed that hemicellulose is easier to be removed with alkalization compared to lignin. X-Ray Diffraction Analysis (XRD) displays higher crystallinity in nanocomposites due to nanoclay.